2018
DOI: 10.1007/s11442-018-1513-x
|View full text |Cite
|
Sign up to set email alerts
|

Spatio-temporal evolution of population and urbanization in the countries along the Belt and Road 1950–2050

Abstract: This paper uses data for the period 1950-2050 compiled by the United Nations Population Division together with methods including spatial autocorrelation analysis, hierarchical cluster analysis and the standard deviational ellipse, to analyze the spatio-temporal evolution of population and urbanization in the 75 countries located along the routes of the Silk Road Economic Belt and the 21st-century Maritime Silk Road, to identify future population growth and urbanization hotspots. The results reveal the followin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
35
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(37 citation statements)
references
References 10 publications
0
35
0
2
Order By: Relevance
“…Most countries in the Belt and Road (BR) region are developing countries with rapid urbanization, high rural poverty rates and serious environmental threats (Y. Liu et al, 2019). Some scientists anticipate an increasing tendency of urbanization dependency in space, imposing greater pressures on urban landscapes and ecosystems in the BR region (H. Liu et al, 2018). The spatiotemporal changes in vegetation greening and land cover types of the BR region were dramatic (Lechner et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Most countries in the Belt and Road (BR) region are developing countries with rapid urbanization, high rural poverty rates and serious environmental threats (Y. Liu et al, 2019). Some scientists anticipate an increasing tendency of urbanization dependency in space, imposing greater pressures on urban landscapes and ecosystems in the BR region (H. Liu et al, 2018). The spatiotemporal changes in vegetation greening and land cover types of the BR region were dramatic (Lechner et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Since the Belt and Road Initiative was put forward, the trade volume between China and related countries has increased sharply. China's rapid economic growth means that more energy and minerals are needed, which will impact the ecological security of exporting countries (Liu et al, 2018a).…”
Section: Multi-regional Telecouplingmentioning
confidence: 99%
“…Research suggests that the world economy became more polarized between 1960 and 1999, and that access to the World Trade Organization did not reduce differences and levels of polarization among member states [ 6 ]. Others argue that levels of urbanization show significant spatial dependence [ 7 , 8 ]. It has also been reported that highly concentrated urbanization might hinder sustainable regional development [ 9 ].…”
Section: Introductionmentioning
confidence: 99%